Comparative Analysis of the Implementation of HR Accounting on Financial Performance at PT. Bank Syariah Indonesia Tbk - Listya Devi Junaidi; Sri Mulyani (LPPM Universitas BSI, 2023)
Human resource accounting has emerged as a result of accounting standards' failure to give management and investors pertinent information. This study aims to compare PT. Bank Syariah Indonesia Tbk's financial performance ratio (profitability ratio) before and after the adoption of human resource accounting. The research method used is descriptive experimental research method. The data used is the company's annual report data for 2020 and 2021. Furthermore, the data is calculated using historical cost data analysis techniques and profitability ratios. The findings from this study indicate an increase in total assets and total equity in the statement of financial position after simulating the application of human resource accounting. This is due to the total value of the net human resource investment that occurs in each year of the existing implementation simulation statement of financial position, so that a new human resource asset account appears in the asset position and retained earnings adjustment in the equity position. While the results of a comparative analysis of financial ratios using return on assets, return on equity, asset utilization, equity multiplier and profit margin show a decline in 2021 but the numbers are relatively small.Â In future research it is expected to add years of research and add other financial ratios so that the results obtained are even better.